Outbreaks of Spodoptera eridania (Lepidoptera: Noctuidae) in tomato plantations in Espírito Santo state, Brazil - Andrade, Gilberto Santos; Czepak, Marcio Paulo; Dalvi, Leandro Pin; Pereira, Fabricio Fagundes; Pratissoli, Dirceu (Agrarian, 2013)
Spodoptera eridania Cramer (Lepidoptera: Noctuidae) has been reported in various crops in recent years in Brazil. The outbreaks of S. eridania were observed in regions of tomato production in the state of Espírito Santo, Brazil. The chemical control used as the main method of control pests, without the agronomic observations of integrated pest management, is a probable cause of such outbreaks in tomato in these regions.